2020
DOI: 10.1186/s13018-020-01749-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the burden of family caregivers of elderly patients with femoral neck fracture: a cross-sectional study

Abstract: Background: This study aimed to study the factors associated with caregiver burden among caregivers of elderly patients with femoral neck fracture. Methods: This cross-sectional study was based on a non-probabilistic sampling of 183 elderly postoperative patients (aged 65 years or older) with femoral neck fracture who were hospitalized in the orthopedic center in our hospital and their family caregivers. Data were collected from January 2016 to June 2019. Patients and family caregivers completed the sociodemog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Due to the lack of advanced medical care in rural areas than in cities, they are forced to travel long distances to obtain medical care for their loved ones. This is consistent with the findings of a study conducted in China by (68) ), which found a significant relationship between caregivers' place of residence and their level of burden. This contrasts with the findings of the study conducted in Egypt by (55) who reported that there were no significant relationships between caregiver burden and caregiver residence, he added that the place where the caregivers lived was not correlated with the level of burden of the caregiver and the place where the caregivers lived of the caregivers was unrelated to the caregiver's level of burden.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the lack of advanced medical care in rural areas than in cities, they are forced to travel long distances to obtain medical care for their loved ones. This is consistent with the findings of a study conducted in China by (68) ), which found a significant relationship between caregivers' place of residence and their level of burden. This contrasts with the findings of the study conducted in Egypt by (55) who reported that there were no significant relationships between caregiver burden and caregiver residence, he added that the place where the caregivers lived was not correlated with the level of burden of the caregiver and the place where the caregivers lived of the caregivers was unrelated to the caregiver's level of burden.…”
Section: Discussionsupporting
confidence: 92%
“…Xiao et al . (2020)[ 21 ] indicated that caregiver-related, patient-related, and system-related factors affected pain management in hip fractures. Brennan et al .…”
Section: Discussionmentioning
confidence: 99%
“…SSRC was confirmed with good reliability and α's coefficient ( 47 , 48 ). Epidemiological studies among the Chinese population have widely used SSRC to examine the relationship between social support and diseases ( 32 , 49 ). Over past decades, studies across the world have employed various tests to determine social support.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also showed high-construct validity and content validity ( 31 ). As a questionnaire to evaluate social support, SSRC has been widely accepted and used in epidemiological studies across China ( 32 ).…”
Section: Methodsmentioning
confidence: 99%